Effectiveness of Lateral Heel Wedge in Patient Suffering from Knee Osteoarthritis - Faim, Zarmina; Khan, Muhammad Kamran; Shah, Wisal; Uzma, Bibi (Poltekkes Kemenkes Jakarta I, 2023)
Background: Knee osteoarthritis, which most commonly affects the medial compartment of the knee, is a chronic joint disorder that imposes a major healthcare burden. As no cure exists, traditional management aims to reduce pain, improve function, and enhance the quality of life while minimizing the adverse effects of therapy. Non-drug conservative interventions are considered the first-line approach to osteoarthritis management. Patients with medial compartment osteoarthritis of the knee typically exhibit genu varum on weight-bearing. This misalignment shifts the mechanical axis medially at the level of the knee joint, increasing the stresses on the medial compartment of the knee and potentially exacerbating knee osteoarthritis. Methods: The study design was a cross-sectional survey to determine the effectiveness of the lateral heel wedge in patients suffering from knee osteoarthritis. This study was conducted at the Pakistan Institute of Prosthetic and Orthotic Sciences in Peshawar. Results: This study concluded that there is a considerable effectiveness of the lateral heel wedge in patients with OA knee. There is some evidence to suggest that they do have some symptomatic effect, and it also shows that the ratio of females to males is high. Additionally, the rate of Knee OA is greater in older age.